US duplex findings of deep chronic venous insufficiency of the lower limbs in 700 Mexican patients - Mauricio Figueroa-Sanchez; Roberto Hernandez-Juarez (Journal of the Mexican Federation of Radiology and Imaging)
Introduction: The ultrasound (US) findings of deep chronic venous insufficiency (CVI) have been insufficiently addressed. This study evaluated the US duplex findings of the deep venous system in Mexican patients with clinically suspected CVI referred by angiologists. Materials and Methods: This cross-sectional study was conducted in patients over 18 years of age with suspected CVI referred by angiologists. The complete protocol included the following US modalities: grayscale, duplex Doppler, color Doppler, power Doppler, and B-flow. The US examination focused on the deep venous system, evaluating parameters such as diameter, compressibility, patency, flow direction, and the presence of venous reflux. Results: We examined 956 limbs from 700 patients with suspected CVI; 485 (69.3%) were women, and 215 (30.7%) were men. Right unilateral US duplex was performed 178 (25.4%), left unilateral in 265 (37.9%), and bilateral in 257 (36.7%). Deep CVI was found in 146 (30.2%) of 485 women and 75 (34.9%) of 215 men, mainly affecting the femoral vein, with a higher prevalence in the left limb in both sexes. No significant differences in the vein diameter were found in patients with or without CVI. Secondary CVI was more common and mainly affected the left limb. Conclusion: In this study, deep CVI was found in about 1 in 3 patients with clinically suspected CVI, with a higher prevalence in men than in women. Secondary CVI was more prevalent. This study of Mexican patients is the first to describe US duplex findings in deep CVI.